Liquid-Phase Hydrogenation of 1-Phenyl-1-propyne on the Pd1Ag3/Al2O3 Single-Atom Alloy Catalyst: Kinetic Modeling and the Reaction Mechanism - Alexander V. Rassolov; Igor S. Mashkovsky; Galina N. Baeva; Galina O. Bragina; Nadezhda S. Smirnova; Pavel V. Markov; Andrey V. Bukhtiyarov; Johan Wärnå; Alexander Yu. Stakheev; Dmitry Yu. Murzin (Nanomaterials, 2021)
This research was focused on studying the performance of the Pd1Ag3/Al2O3 single-atom alloy (SAA) in the liquid-phase hydrogenation of di-substituted alkyne (1-phenyl-1-propyne), and development of a kinetic model adequately describing the reaction kinetic being also consistent with the reaction mechanism suggested for alkyne hydrogenation on SAA catalysts. Formation of the SAA structure on the surface of PdAg3 nanoparticles was confirmed by DRIFTS-CO, revealing the presence of single-atom Pd1 sites surrounded by Ag atoms (characteristic symmetrical band at 2046 cm−1) and almost complete absence of multiatomic Pdn surface sites (<0.2%). The catalyst demonstrated excellent selectivity in alkyne formation (95–97%), which is essentially independent of P(H2) and alkyne concentration. It is remarkable that selectivity remains almost constant upon variation of 1-phenyl-1-propyne (1-Ph-1-Pr) conversion from 5 to 95–98%, which indicates that a direct alkyne to alkane hydrogenation is negligible over Pd1Ag3 catalyst. The kinetics of 1-phenyl-1-propyne hydrogenation on Pd1Ag3/Al2O3 was adequately described by the Langmuir-Hinshelwood type of model developed on the basis of the reaction mechanism, which suggests competitive H2 and alkyne/alkene adsorption on single atom Pd1 centers surrounded by inactive Ag atoms. The model is capable to describe kinetic characteristics of 1-phenyl-1-propyne hydrogenation on SAA Pd1Ag3/Al2O3 catalyst with the excellent explanation degree (98.9%).